ANALYSIS OF QUALITY IN RICE SEEDS DISTRIBUTION FOR A SEED DRILL - MELO, R.P.; FERNANDES, F.R.B.; DO NASCIMENTO, H.C.F.; MAIA, C.L.; ALBIERO, D. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The planters have an important role when one takes into consideration that the process of sowing must be done correctly, ensuring adequate plant population at the end stand. In this sense one of the factors that influence this process is the uniformity of seed distribution. In agriculture is difficult to determine all the points that interfere during agricultural operations, so the qualities of tools are presented as an alternative to ensure proper performance of the process depending on the critical factors. This study aimed to evaluate the rice seed distribution density function of two theoretical speeds of displacement 4 and 8 km.h-¹ to one seed drills. The experiment was conducted in the experimental area of the Department of Agriculture of the Federal University of Ceara Engineering, Campus do Pici, Fortaleza, Ceara in a soil classified as Red- Yellow Ultisol. The drill was adjusted to obtain the density of 80g of rice seeds / m. The process of sowing was carried out at a distance of 50m in length. The evaluation of the distribution of the seeding density was performed according to the recommendations Fields (1998). Data were analyzed using Minitab Software - Version 16. The rice seed density distribution is influenced with increasing speed.